2013
DOI: 10.1371/journal.pone.0061808
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Biocontrol Activity of Pseudomonas fluorescens Strain X Reveals Novel Genes Regulated by Glucose

Abstract: Pseudomonas fluorescens strain X, a bacterial isolate from the rhizosphere of bean seedlings, has the ability to suppress damping-off caused by the oomycete Pythium ultimum. To determine the genes controlling the biocontrol activity of strain X, transposon mutagenesis, sequencing and complementation was performed. Results indicate that, biocontrol ability of this isolate is attributed to gcd gene encoding glucose dehydrogenase, genes encoding its co-enzyme pyrroloquinoline quinone (PQQ), and two genes (sup5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
1
15
0
1
Order By: Relevance
“…Thus, fl agellated bacteria would be expected to swim or to swarm under certain soil saturation levels. Recent studies demonstrated that displacement of Bradyrhizobium japonicum is achieved in 80% saturated soil (Covelli et al, 2013) while Pseudomonas fl uorescens strain X (Kremmydas et al, 2013) displayed a fast movement in 50% saturated soil (Fig. 1).…”
Section: Swarming Bacteria Dispersed Over Fungimentioning
confidence: 94%
“…Thus, fl agellated bacteria would be expected to swim or to swarm under certain soil saturation levels. Recent studies demonstrated that displacement of Bradyrhizobium japonicum is achieved in 80% saturated soil (Covelli et al, 2013) while Pseudomonas fl uorescens strain X (Kremmydas et al, 2013) displayed a fast movement in 50% saturated soil (Fig. 1).…”
Section: Swarming Bacteria Dispersed Over Fungimentioning
confidence: 94%
“…The upregulation of the pqq and gcd genes in the gacS mutant was confirmed by qPCR (not shown). In Pseudomonas and other Gram‐negative bacteria, gluconic acid biosynthesis has been shown to be dependent on PQQ as an enzymatic cofactor of the membrane‐bound quinoprotein, glucose dehydrogenase (Gcd) (Goldstein, ; Kaur et al ., ; de Werra et al ., ; Kremmydas et al ., ; Ponraj et al ., ). Gcd acts as a glucose sensor and catalyses glucose into gluconic acid by periplasmic oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Like PA23, P . chlororaphis 189 contained an array of biosynthetic pathways capable of producing metabolites involved in biocontrol, including hydrogen cyanide (6), phenazine (7), pyocin (8), pyrroloquinoline quinone (9), and cell wall degradative enzymes. Genes conferring the ability to produce surfactants and form biofilms (10) were also found.…”
Section: Genome Announcementmentioning
confidence: 99%